2009
DOI: 10.1007/s12044-009-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Relations between bilinear multipliers on ℝ n , % MathType!MTEF!2!1!+- % feaagaart1ev2aaatCvAUfKttLearuqr1ngBPrgarmWu51MyVXgatC % vAUfeBSjuyZL2yd9gzLbvyNv2CaeHbd9wDYLwzYbItLDharyavP1wz % ZbItLDhis9wBH5garqqtubsr4rNCHbGeaGqipC0xg9qqqrpepC0xbb % L8F4rqqrFfpeea0xe9Lq-Jc9vqaqpepm0xbba9pwe9Q8fs0-yqaqpe % pae9pg0FirpepeKkFr0xfr-xfr-xb9adbaqaaeGaciGaaiaabeqaam % aaeaqbaaGcbaWefv3ySLgznfgDOjdarCqr1ngBPrginfgDObcv39ga % iyaacqWFtcpvaaa!4660! $$ \mathbb{T} $$ n and ℤ n

Abstract: In this paper we prove the bilinear analogue of de Leeuw's result for periodic bilinear multipliers and some Jodeit type extension results for bilinear multipliers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In the year of 1985, Rubio de Francia [18] proved above inequality (4) for the case of arbitrary sequence of disjoint intervals in R. In both the previous results p ≥ 2 is an optimal condition.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the year of 1985, Rubio de Francia [18] proved above inequality (4) for the case of arbitrary sequence of disjoint intervals in R. In both the previous results p ≥ 2 is an optimal condition.…”
Section: Introductionmentioning
confidence: 85%
“…For this we will use the ideas developed in [11], adapted to our setting. We would like to refer the reader to [4], [2], [3], [8] for some work related to transference techniques in the bilinear settings.…”
Section: Relation Between B P (R) and L P (R) Multipliersmentioning
confidence: 99%
See 1 more Smart Citation
“…We will use a result proved in [1], where it is shown that the periodic extension of a compactly supported bilinear symbol is again a bilinear symbol for a bounded operator. …”
Section: Erratamentioning
confidence: 99%